Features of the mechanical behavior of ultrafine-grained and nanostructured TiNi alloys. (2017) - Gunderov, Dmitry; Churakova, Anna; Lukyanov, Aleksandr; Prokofiev, Egor; Pushin, Vladimir; Kreitcberg, Alena; Prokoshkin, Sergey
Abstract: The article presents the results of the study on the mechanical behavior of ultrafine-grained (UFG) and nanocrystalline (NC) TiNi alloys produced by severe plastic deformation (SPD), using the techniques of high pressure torsion (HPT) and annealing. The features of the microstructure and deformation behavior of the NC and UFG alloy have been studied. The amorphous and NC TiNi alloy exhibits enhanced strength. Variation of the post-deformation annealing temperature of the HPT-processed samples can be used for the formation of a structure with various grain sizes and different levels of strength and ductility. Although under deformation the alloy passes to the martensitic state, the dependence of yield stress of TiNi on grain size D in the range of 30 µm to 20 nm (HPT + annealing at 400°C) corresponds to the Hall-Petch relation, and yield stress is determined by the size of the austenite grain.